2013
DOI: 10.7150/ijbs.5306
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid and Transcriptome Profiling of Longissimus Dorsi Muscles between Pig Breeds Differing in Meat Quality

Abstract: Fat and lean pig breeds show obvious differences in meat quality characteristics including the fatty acid composition of muscle. However, the molecular mechanism underlying these phenotypes differences remains unknown. This study compared meat quality traits between Lantang (a Chinese indigenous breed) and Landrace (a typical lean breed). The Lantang pigs showed higher L* values and intramuscular fat content, lower pH45min, pH24h and shear force in longissimus dorsi (LD) muscle than Landrace (P < 0.05). Fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
46
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 30 publications
11
46
1
2
Order By: Relevance
“…To date, differences between breeds in SCD gene expression have not been widely examined, and all available publications are strictly connected with the LD muscle. Our results are in agreement with those of Yu et al (2013) who found that the greater SCD gene expression in the LD muscle of Lantang than in Landrace pigs was accompanied by higher IMF, MUFA and PUFA contents in this muscle. Opposite results were obtained by Gao et al (2011), who reported lower SCD expression in Northeastern Indigenous pigs having a higher IMF content, but the animals were slaughtered on day 150 regardless of their final BW.…”
Section: Expression Of Genes Encoding Enzymes Connected With Fat Metasupporting
confidence: 83%
See 3 more Smart Citations
“…To date, differences between breeds in SCD gene expression have not been widely examined, and all available publications are strictly connected with the LD muscle. Our results are in agreement with those of Yu et al (2013) who found that the greater SCD gene expression in the LD muscle of Lantang than in Landrace pigs was accompanied by higher IMF, MUFA and PUFA contents in this muscle. Opposite results were obtained by Gao et al (2011), who reported lower SCD expression in Northeastern Indigenous pigs having a higher IMF content, but the animals were slaughtered on day 150 regardless of their final BW.…”
Section: Expression Of Genes Encoding Enzymes Connected With Fat Metasupporting
confidence: 83%
“…This could be connected with changes in the level of SCD mRNA, the first enzyme converting SFA to MUFA. Moreover, C2C12 myoblasts with overexpression of SCD are also characterised by increased amounts of such PUFA as: LA, ALA, arachidonic acid (C20:4 n-6) and EPA (Yu et al, 2013). In our experiment, SCD gene expression in LD and BF muscles was greater in L990 pigs, which also had higher MUFA and PUFA contents in these muscles.…”
Section: Expression Of Genes Encoding Enzymes Connected With Fat Metasupporting
confidence: 52%
See 2 more Smart Citations
“…ND2 variation is significantly associated with the pectoral muscle fat content of chickens (Lu et al 2014). Previous reports showed that the PUFA levels were closely associated with alteration of expression of the body lipid metabolism related genes as hepatic LPIN1 transcript was found to be negatively regulated by the dietary PUFA proportion and its expression of mRNA levels was correlated with the PUFA proportion in muscle (Martin et al 2007;Yu and Shu 2013), FADS2 gene expression level in adipocyte was reported to be negatively correlated with 20:5n-3 and 20:4n-6 (Ralston et al 2015). However, literature about the effects of PUFA on the expression of ND2 in broilers is lacking.…”
Section: Introductionmentioning
confidence: 96%